HGG-09. FIRST LINE THERAPY OF PEDIATRIC GLIOBLASTOMA WITH LAROTRECTINIB. (4th December 2020) - Alharbi, Musa; Mobark, Nahla Ali; Balbaid, Ali Abdullah O; Alanazi, Fatmah A; Aljabarat, Wael Abdel Rahman; Bakhsh, Eman A K; Turkistani, Murad; Abedalthagafi, Malak
Abstract: PURPOSE: In this case report, we document new recommendations for the treatment of pediatric glioblastoma based on a genetic understanding of the disease. PATIENTS AND METHODS: A Saudi girl aged 18 months presented with a history of right sided weakness and partial seizures. MRI revealed the presence of large complex left frontal tumor. Craniotomy and gross total resection were performed. post-operatively The patient showed excellent recovery with no neurological deficits. Pathology reports confirmed glioblastoma (GBM). Due to the expected poor survival, the patient's family declined standard therapy, including chemotherapy and/or radiation therapy. RESULTS: Molecular analysis showed positive fusion mutations for ETV6-NTRK3 making the patient an ideal candidate for larotrectinib, an oral tyrosine kinase (TRK) inhibitor. Unfortunately, follow-up MRI showed local tumor recurrence at 3-months post-surgery. The family agreed to the initiation of oral larotrectinib as a less invasive therapy. The patient tolerated Larotrectinib very well with no reported side effects. Follow up MRI was performed 8-weeks post-larotrectinib treatment and showed significant tumor regression, indicating an excellent treatment response. CONCLUSION: This case highlights how TRK-inhibitors can be integrated as a first-line therapy for pediatric high grade GBMs harboring TRK-fusions. We also highlight the need for the integration of genomic profiling and molecular analysis into the routine histopathologic analyses of pediatric patients with malignant primary intracranial tumors, to detect any genetic mutations that can be targeted with available therapies to avoid the morbidity associated with non-precision conventional therapies.